2012 IEEE 62nd Electronic Components and Technology Conference 2012
DOI: 10.1109/ectc.2012.6248798
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D interconnect routing and stacking strategy to optimize high speed signal transmission for memory on logic

Abstract: 3D stacking technologies are electrically studied to predict high speed data transmission for memory on logic applications. Maximal frequency of bandwidth for memoryprocessor and processor-BGA channels are extracted and compared for Face to Face and Face to Back 3D stacking and between an interposer technology. Using expected electrical specifications of Wide IO applications in terms of data rates, a roadmap is proposed in accordance to the integration density, carried out by the TSV density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It turns out that the most chip-to-chip interconnections are smaller than 5 mm and the shielded interconnections are running with 200 MHz. In [3] different stacking strategies, including the side-by-side approach, are compared in terms of density and length and their resulting (theoretical) achievable bandwidth. Differential transmission lines with different concepts for the ground shielding to the substrate are compared with EM simulations in [4].…”
Section: State Of the Artmentioning
confidence: 99%
“…It turns out that the most chip-to-chip interconnections are smaller than 5 mm and the shielded interconnections are running with 200 MHz. In [3] different stacking strategies, including the side-by-side approach, are compared in terms of density and length and their resulting (theoretical) achievable bandwidth. Differential transmission lines with different concepts for the ground shielding to the substrate are compared with EM simulations in [4].…”
Section: State Of the Artmentioning
confidence: 99%
“…In [9] a theoretical circuit analysis showed that a 16 mm-long (RDL) interconnect on silicon interposer has a bandwidth of 535 MHz. However, as shown in the model proposed by [10], this frequency limit can be at least doubled by using a 2 µm width micro-strip line on a silicon interposer with 2 µm-thick bimetal BEOL.…”
Section: Introductionmentioning
confidence: 99%
“…It includes technological developments as the Through Silicon Via technology for 3D-WLP and 3D-IC, Cu Pillars and flip chip. It also deals with electromagnetic simulations [5], High Frequency characterization of TSV, Cu-Pillars and Redistribution Layers (RDL), up to 40 GHz [6], and compact modeling [7].…”
Section: Introductionmentioning
confidence: 99%